A case of pyogenic liver abscesses in a previously healthy adolescent man. (10th November 2014) - Mentel, Dena A.; Cameron, Danielle B.; Gregg, Shea C.; Cholewczynski, Walter; Savetamal, Alisa; Crombie, Roselle E.; Possenti, Paul P.; Atweh, Nabil A.
Abstract : An 18-year-old, previously healthy man admitted with abdominal pain, high-grade fevers, nausea and emesis was found to have multiple hepatic abscesses. Aspiration cultures grew Fusobacterium necrophorum, a rare bacterium causing potentially fatal liver abscesses in humans. Following sequential percutaneous drainages and narrowing of antibiotics, the patient was discharged on a 6-week antibiotic course and showed no signs of infection. A week after presentation it was discovered that he had experienced upper respiratory symptoms and sore throat prior to presentation. Because oropharyngeal infections are a potential source of bacteremia, they must be considered in the differential diagnosis of patients presenting with hepatic abscesses and no evidence of immunocompromise.